Presence of Ethical, Aesthetic and Religious Keys in the Creation of Possible Literary Worlds - María Victoria Hernández Ruiz (Cauriensia, 2022)
Literary works have structures that articulate the possible worlds represented in them using ethical, aesthetic, and religious keys -mimeses of these structures in the real effective world- so that the greater or lesser presence of these keys determines whether the work is coherent, plausible, and meaningful for the reader. Literary theories have omitted the study of this section of reality present in the structure of the works and, therefore, in this article we intend to systematise and describe, using the semantic theory of possible worlds, the functioning of these structures in the processes of representation, creation, and reception of a work of fiction. We also provide a proposal for a model of analysis that ratifies the presence of these articulating structures of the fictional world and regulators of the interactions of the possible characters among themselves, with the world they inhabit and with transcendence. With this research we want to confirm the need to include ethical, aesthetic and religious structures within the theory of literature and to offer a rich and fruitful model of analysis.